Small Cities and the Theory of Growth Poles: A New Perspective - Santos, Vitória Alves dos; Rezende, Wagner de Souza (National Journal of City Management, 2024)
This paper intends to reinterpret the Theory of Growth Poles, or Polarization Theory, formulated by François Perroux in the 1950s, to analyze the urban development of small cities. The theory suggests that the formation of urban centralities occurs heterogeneously at specific points in the territory, whose growth vectors are influenced by the actions of global socio-economic networks in local political arenas. These cities act as force fields that attract and stimulate growth in surrounding regions. This study aims to identify and analyze the effects of growth poles on the urban condition of small cities in the state of Goiás, Brazil, using criteria adapted from Perroux (1981) and reinterpreted for application in the context of cities located in southern Goiás. This is a theoretical work that, through a bibliographical review, presents a critical re-reading of the urban networks formed by city-regions, which we believe is relevant to the discussion on urban and regional planning in Brazil. The results of mapping the growth poles in the state of Goiás show social, cultural, political, and economic asymmetries in the territorial configurations. They reveal significant heterogeneity, indicating the need to redefine the criteria for their definition. This article aims to contribute to urban studies by identifying new agents influencing the territory, considering specific social, geographical, and economic contexts. The intention is to contribute to urban studies by listing new main agents influencing the territory, considering their contexts.
Keywords: City-region; Urban Networks; Growth Poles